2014
DOI: 10.1002/num.21925
|View full text |Cite
|
Sign up to set email alerts
|

A three‐level linearized compact difference scheme for the Ginzburg–Landau equation

Abstract: A high-order finite difference method for the two-dimensional complex Ginzburg-Landau equation is considered. It is proved that the proposed difference scheme is uniquely solvable and unconditionally convergent. The convergent order in maximum norm is two in temporal direction and four in spatial direction. In addition, an efficient alternating direction implicit scheme is proposed. Some numerical examples are given to confirm the theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Hao et al [29] suggested a high-order finite difference method for the 2D complex GL equation. They proved that the proposed difference scheme is uniquely solvable and unconditionally convergent.…”
Section: An Introduction About Hoc-adi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hao et al [29] suggested a high-order finite difference method for the 2D complex GL equation. They proved that the proposed difference scheme is uniquely solvable and unconditionally convergent.…”
Section: An Introduction About Hoc-adi Methodsmentioning
confidence: 99%
“…The convergent order in maximum norm was two in temporal direction and four in spatial direction. In addition, an efficient alternating direction implicit scheme was proposed in [29].…”
Section: An Introduction About Hoc-adi Methodsmentioning
confidence: 99%
“…To construct a compact difference scheme for solving (1.1)–(1.4), the following lemmas are needed.Lemma () Suppose u ( x ) C 6 [ x j 1 , x j + 1 ] , then we have left u ( x j 1 ) 2 u ( x j ) + u ( x j + 1 ) h 2 = 1 12 [ u ( x j 1 ) + 10 u ( x j ) + u ( x j + 1 ) ] + h 4 360 u ( 6 ) ( normalξ j ) u ( x j 1 ) u ( x j + 1 ) 2 h = 1 6 [ u ( x j 1 ) + 4 u ( x j ) + u ( x j + 1 ) ] + h 4 120 u ( 6 ) ( normalζ j ) where normalξ j , normalζ j ( x j 1 , x j + 1 …”
Section: The Compact Difference Scheme and Computational Methodsmentioning
confidence: 99%
“…In [4, 12-14, 18-21, 30-36], many conservative finite difference schemes were used for various nonlinear wave equations. Recently, there has been growing interest in high-order compact (HOC) methods for solving partial differential equations (PDEs) [30][31][32][33][34][37][38][39][40][41][42][43][44]. Therefore, a mass-conservative and high-order compact finite difference scheme which can preserves the solution to the SRLW equation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation of the model is playing an important role in understanding the behaviors of the equations in both non‐fractional and fractional cases. In the context of standard nonlinear GLE, various numerical methods have been developed, including spectral method , notably finite difference method etc. In the setting of fractional version, however, the numerical study is rather young and scarce.…”
Section: Introductionmentioning
confidence: 99%